FORMULASI SEDIAAN GEL ANTISEPTIK FRAKSI POLAR DAUN KESUM (Polygonum minus Huds) - ., Syari Wahyuni Ansiah (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Antiseptic is usually use to against microorganism at the surface of body.One of the plant that has antibacterial activity is kesum (Polygonum minus Huds).The purpose of this experiment is to know which antiseptic gel containing polarfraction of kesum leaves that show the best antiseptic power and physic andchemical stability.This research included antibacterian activity test of polarfraction, formulation gel of polar fraction, effectivity test of polar fraction gel andstability test. Data that has been analyzed statistically by using One Way ANOVAtest. The test result showed that kesum leaves polar fraction at concentration 5%,10% dan 15% gave antibacterial activity and then they were formulated inantiseptic gel product. The result showed that kesum leaves polar fraction gel hadantiseptic power. The three gels had similar stability in organoleptic test. Gel IIIwith 15% concentration of polar fraction underwent the least of viscositydecreasing. Gel II with 10% concentration of polar fraction underwent the least ofthicking ability decreasing, pH, and spread ability increasing. Keyword : kesum leaves, gel, antiseptic, Escherichia coli